FREQUENCY OF OSTEOPOROSIS IN PATIENTS WITH CIRRHOSIS DUE TO HEPATITIS B AND HEPATITIS C: A STUDY OF 100 CASES - Javed, Mohammad; Saeed, Arif; Khan, Ijaz Mohammad; Hameed, Khalid; Rehman, Sher; Khattak, Abbas Khan; Ahmad, Iqbal; Khan, Shabir Ahmad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Osteoporosis is the disease of bone that affected King David of Israel 3000 years ago. This condition is no longer considered to be due to aging alone and is increasingly recognised as a major health concern and accounts for about 1.5 million fractures annually in United States. Objective of this study was to see the frequency of osteoporosis in patients with cirrhosis due to Hepatitis B and C, and any correlation between the Bone Mineral Density (BMD) and duration and stage of the liver disease. Methods: The study was conducted in the Department of Gastroenterology, Postgraduate Medical Institute, Hayatabad Medical Complex, Peshawar, from January 2008 to December 2008. All patients from the OPD or Ward fulfilling the criteria and consenting were included. Physical examination, with special emphasis on any signs of chronic liver disease was performed. Full blood count, platelet count, prothrombin time and INR, liver function tests including serum albumin, and renal function tests were done on all patients. Viral serology was checked for those patients who were either newly diagnosed as cirrhotic or were cirrhotic but not screened for viral markers. Abdominal sonogram was recorded on all patients. The Child's score was calculated for each patient using the clinical and lab parameters. The BMD was calculated for all patients using computer based ultrasound probe. Calcaneum was used for evaluation of BMD. The information collected was entered on structured data collection sheets and was analysed using SPSS version 11. Results: Osteoporosis was found in 26% of subject and osteopenia in 42%, while 32% had BMD in the normal range. The mean T score was -1.483 (±1.29). The mean duration of liver disease was 3.77 (±1.56) year. Majority of the patients (81%) were in Child's Class C, followed by Class B and A (16% and 3% respectively). Fiftynine percent of the patients were males with a mean age of 37.65 years, while 41% were females with mean age of 37.76 years. Conclusion: Osteoporosis is a common finding in patients with cirrhosis due to Hepatitis B and C. Osteoporosis is more frequent in patients with long duration of liver disease but there is no significant correlation between the aetiology or severity of liver disease and osteoporosis. Keywords: BMD, T score, Child's score, Cirrhosis, Hepatitis B, Hepatitis C, Osteoporosis